TIPOLOGI DAN POLA PENANGANAN PERMUKIMAN KUMUH DI KOTA BONTANG (The Typology and Patterns of Slum Improvement Management in Bontang City) - Amos Setiadi (Diponegoro University, 2014)
Started as a fishing settlement area in Bontang Kuala Village, the City of Bontang has been growing very rapidly. However, despite this growth people's standard of living has been decreasing in terms of environmental quality, income as well as sheltering with the emergence of slum areas. These conditions greatly affect the physical, social, cultural and economic aspects of life. The management of slum areas in Bontang City becomes strategic because slums are integrated with the rest of the city including the downtown area and urban growth centers, as well as with the other areas in the vicinity, such as industrial, commercial, warehousing, and office areas. Therefore, it is necessary to identify the characteristics of the slum areas. The identification methods do not discriminate the distribution of slum areas. The criteria used include non-economic vitality, regional economic vitality, land ownership status, infrastructure and facility conditions, local government’s commitment, and handling priorities. Environmental assessment of the slums was done by assigning a weighting system to each of the above criteria. The determination of the weights of the criteria is relative and depends on the individual and group preferences in looking at the influence of each criterion. The improvement or treatment patterns appropriate to be applied in Bontang City should be in accordance with the site characteristics. Locations with high-scale slum category (HS) requires the curative pattern while those with moderate category (MS) should take reductive treatment, and slum areas with low-scale category (LS) will require preventive treatment.